The role of Matrix metalloproteinase (MMP-9) and its tissue inhibitor (TIMP1) in Cutaneous Leishmaniasis patients and their role in prognosis - Hassan, Ghuffran Muhammed; Ali, Hayder Zuhair; Hussein, Watheq Muhammed (Iraqi Journal of Science, 2025)
Cutaneous leishmaniasis (CL) is a widespread, yet often overlooked, parasitic disease caused by the Leishmania protozoan, which is prevalent in numerous countries, including Iraq. This condition is marked by the appearance of skin lesions on various exposed areas of the body. In most old-world regions, sodium stibogluconate (SSG) is the classical widely used drug to treat CL. The progression of skin ulceration is controlled by different inflammatory modulators including cytokines and enzymes. In this study, the possible role of the enzyme Matrix metalloproteinase9 (MMP-9) and its inhibitor Metallopeptidase inhibitor-1 (TIMP-1) as immunological markers was evaluated in CL patients suffering from cutaneous leishmaniasis before and after treatment by sodium stibogluconate.  A total of 161 serum samples of newly diagnosed individuals and patients undergoing Pentostam injections were collected from an endemic area of Diyala, east central Iraq. The level of MMP-9 and TIMP-1 was evaluated in the serum of recently diagnosed CL patients and previously diagnosed CL patients who were undergoing five stages of sodium stibogluconate injections. The results have shown that among the study groups, the recently infected individuals who received no treatment showed significantly elevated levels of both MMP-9 (mean: 20.864 ng/ml) and TIMP-1 (mean: 1193.748 ng/ml). Additionally, the concentration of TIMP-1 was significantly raised in the groups undergoing pentostam treatment from injection-1 to injection-4, when compared to the control individuals. The current findings highlight important insights into the studied serum markers to follow up the development of the treatment in cutaneous leishmaniasis patients.